Pengaruh DEA dan Waktu Dipping terhadap Nilai Band Gap Lapisan Tipis CuSnO3 - Rizka, Futtyhat; Sanjaya, Hary (Lembaga Yasin AlSys, 2023)
CuSnO3 is one of the semiconductor materials that can be used in the manufacture of thin film. CuSnO3 is an amorphous semiconductor with a band gap of 2.0-2.5 eV. Dip-coating is one method that can be used to synthesize a thin film of CuSnO3. This study aims to see the effect of DEA additives and dipping time on the band gap value of a thin film of CuSnO3. The results of a thin film of CuSnO3 using the dip-coating method with DEA variations of 1 ml, 1.5 ml, and 2 ml as additives, obtained band gap values of 2.55 eV, 2.41 eV, and 2.31 eV. The larger the volume of DEA, the smaller the band gap value produced. At dipping times of 10 minutes, 15 minutes, and 20 minutes, band gap values of 2.58 eV, 2.31 eV, and 2.26 eV were recorded. The longer the time it takes to dye, the smaller the band gap value produced.